Kekuatan Pembuktian dan Kepastian Hukum Akta Hibah Tanah: antara Akta Otentik PPAT dan Surat di Bawah Tangan - Najati, Fia Agustina; Silviana, Ana (Riwayat: Educational Journal of History and Humanities, 2025)
Grant is a legal act carried out voluntarily and gratuitously by a someone to another living individual. In practice, many gifts are executed without proper legal procedures, particularly without using a notarial deed, which can lead to disputes and legal uncertainty. This study aims to examine the urgency of executing a gift deed through a notary as a legal protection for the recipient, as well as the notary's role in ensuring the validity and legal strength of the deed. The research uses a normative juridical method with a conceptual and case approach. The findings indicate that a gift deed made before a notary has perfect evidentiary strength, provides legal certainty, and is a mandatory administrative requirement for land title transfer. In contrast, a gift based on a private deed lacks strong legal standing and is prone to disputes. Therefore, the notary plays a crucial role in ensuring legality, validity, and legal protection for the recipient of the gift.